Automatic Leaf Epidermis Assessment Using Fourier Descriptors in Texture Images - Silva, Nubia Rosa da; Silva Oliveira, Marcos William da; Almeida Filho, Humberto Antunes de; Souza Pinheiro, Luiz Felipe [UNESP]; Kolb, Rosana Marta [UNESP]; Bruno, Odemir Martinez (Bio-protocol, 2017)
The identification of plant species is not a trivial task, since it is carried out by experts and depends on the presence of fruits, flowers and leaves. However, fruits and flowers are not available throughout the year, while leaves are accessible most of the year. In order to assist the specialized work of species identification, methods of texture image analysis are used to extract characteristics from samples of imaged leaves and thus predict the species. Texture image analysis is a versatile and powerful technique able to extract measurements from patterns in the images. Using this technique, recent research has found a close relationship between texture and plant species (da Silva et al., 2015 and 2016). Here, we describe the procedure to extract texture features from microscopic images of leaves using Fourier (Cosgriff, 1960; Azencott, 1997; Gonzalez and Woods, 2006). It is important to highlight that other methods for texture extraction can be used as well. This protocol is split into two parts: (A) leaf epidermal dissociation and (B) automatic method for leaf epidermal image analysis.
Keywords: Epidermis dissociation; Stomata visualization; Plant identification; Leaf epidermis; Texture image analysis